Effect of MgO sintering additive on mullite structures manufactured by fused deposition modeling (FDM) technology. Issue 13 (October 2021) - Sarraf, Fateme; Abbatinali, Edoardo; Gorjan, Lovro; Sebastian, Tutu; Colombo, Paolo; Churakov, Sergey V.; Clemens, Frank
Highlights: MgO sintering additive promoted densification of FDM printed mullite at 1600°C. MgO avoids difference in mechanical properties due to printing orientation. Spherical pores below 180°C resulted from cross-linking of the preceramic polymer. Spherical pore size is affected by the printed wall thickness. Abstract: An optimized recipe for 3D printing of Mullite-based structures was used to investigate the effect of MgO sintering additive on the processing stages and final ceramic properties. To achieve dense 3:2 mullite, ceramic filaments were prepared based on an alumina powder, a methyl silicone resin, EVA elastomeric binder and MgO powder. Using 1 wt% MgO and a dwell time of 5 h at 1600 °C, a dense mullite structure could be obtained from filaments with a diameter of 1.75 mm. Ceramic structures with and without sintering additive were printed in vertical and horizontal direction, to investigate the effect of printing direction on mechanical strength after sintering. Using four-point bending test, it was demonstrated that by using MgO, the printing orientation did not affect the mechanical strength significantly anymore. The low Weibull modulus could be explained by the closed porosity that emerge during the degassing of the preceramic polymer due to cross-linking.